2020
DOI: 10.3390/ijerph17051683
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Health Literacy, Quality of Life, and Subjective Health: Results of a Cross-Sectional Study in a Rural Region in Germany

Abstract: Low health literacy is associated with poorer health and quality of life. An open question is whether a regional integrated healthcare system whose management strives to enable and empower its members with regard to health issues can contribute to a higher level of health literacy in the population. Against this background, in a cross-sectional study we surveyed a random selection of members of an integrated healthcare system in southwestern Germany (n = 180). The standardized questionnaire included, inter ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 27 publications
5
28
0
Order By: Relevance
“…Multivariate analysis showed that only the education level was associated with HL among the three sociodemographic characteristics. This is consistent with other studies [2,4,5,10,20,[49][50][51][52][53] and the World Health Organisation's statement that consider people with low level of education as a vulnerable group with a scarce HL [2].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Multivariate analysis showed that only the education level was associated with HL among the three sociodemographic characteristics. This is consistent with other studies [2,4,5,10,20,[49][50][51][52][53] and the World Health Organisation's statement that consider people with low level of education as a vulnerable group with a scarce HL [2].…”
Section: Plos Onesupporting
confidence: 92%
“…Health behaviour measured by GSE and health status measured by EQ-VAS were positively correlated with HL as expected [2,53,54].…”
Section: Plos Onesupporting
confidence: 75%
“…The results of many studies conducted among adult individuals in different countries have shown that those more likely to have low HL levels are older adults, unemployed people, individuals with low educational and low-income levels [ 37 39 ]. Furthermore, it has been revealed that those who evaluate their own health as bad also have a low level of HL [ 5 , 36 , 40 ]. These findings, indicating that some social groups have low levels of HL, seem to show that there are various social factors involved in HL.…”
Section: Discussionmentioning
confidence: 99%
“…In "Inclusion of People with Intellectual Disabilities in Health Literacy", Latteck and Bruland [85] present findings from three different studies on the health literacy of particular vulnerable groups. Ehmann et al [86] give information to guide future work in "The Relationship between Health Literacy, Quality of Life, and Subjective Health: Results of a Cross-Sectional Study in a Rural Region in Germany", which will be of particular relevance to a regional integrated healthcare system. Sykes et al [87] give insights on health literacy on the topic of infertility in "Multidimensional eHealth Literacy for Infertility", considering the concept of eHealth literacy in individuals and couples in relation to infertility.…”
Section: Community Level: Tailoring By Culture/topic/population Needsmentioning
confidence: 99%